A Study of Electric Field Effect on Melting of Octadecane - Orlovskaya, S.G.; Karimova, F.F.; Shkoropado, M.S. (Physics and Chemistry of Solid State, 2016)
A new approach is developed to study melting kinetics of n-Octadecane. Modelling of heat transfer during the melting of solid particle is described. The calculation results are in good agreement with experimental data on melting duration. The effect of applied electric field on melting kinetics is studied. Almost twofold increase of melting time is found in an electric field of strength E = 82 kv/m. In addition a rotation of a solid core inside a melt is observed, which is a manifestation of Quinke effect. A droplet shape evolution during phase transition is described. It is shown that initially elongated particle is almost spherical near the melting point and elongates again with the temperature rise. This shape evolution is explained by non-monotonous change of surface tension and is connected with rotational phase. Thus a possibility is shown to control a melting rate of normal alkanes using electric field.